Non-litigation Settlement of Domestic Violence Cases with Alternative Criminal Case Resolution (Study in Segaran Village, Batujaya Karawang District) - Saputra, Ade Rizki; Gunati, Mira; Wartawan, W.; Kurniati, Hj. Yeti; RAS, Hj. Hernawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research investigates the process of resolving cases of domestic violence (KDRT) in a non-litigation manner with alternative resolution of criminal cases in Segaran Village, Batujaya District, Karawang. A qualitative approach is used to understand the dynamics of conflict, the factors that influence resolution, and the effectiveness of the process. Through in-depth interviews and participatory observation, the research results highlight the importance of community involvement, inter-institutional collaboration, and community understanding of domestic violence. These findings contribute to the development of more effective and sustainable conflict resolution strategies at the local level